Short-term and long-term memory analysis of learning using 2D and 3D educational contents. Issue 11 (1st November 2016) - Muhammad, Ghulam; Hussain, Muhammad; Al-Hammadi, Muneer; Aboalsamh, Hatim; Mathkour, Hassan; Malik, Amir Saeed
ABSTRACT: The effect of 2D and 3D educational content learning on memory has been studied using electroencephalography (EEG) brain signal. A hypothesis is set that the 3D materials are better than the 2D materials for learning and memory recall. To test the hypothesis, we proposed a classification system that will predict true or false recall for short-term memory (STM) and long-term memory (LTM) after learning by either 2D or 3D educational contents. For this purpose, EEG brain signals are recorded during learning and testing; the signals are then analysed in the time domain using different types of features in various frequency bands. The features are then fed into a support vector machine (SVM)-based classifier. The experimental results indicate that the learning and memory recall using 2D and 3D contents do not have significant differences for both the STM and the LTM.